Organizational Fit 2012
DOI: 10.1002/9781118320853.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Person–Organization Fit, Organizational Citizenship, and Social‐Cognitive Motivational Mechanisms

Abstract: Person-organization (PO) fit provides an integrative mechanism for examining the linkages between people and the organizations for which they work (Chatman, 1989;Kristof, 1996). Previous research has demonstrated that PO fit is associated with a wide range of positive outcomes for both employees and employers (see KristofBrown et al., 2005). Citizenship performance (e.g., Cable and DeRue, 2002;Lauver and Kristof-Brown, 2001) and motivation are two important outcomes (Bretz and Judge, 1994;Mitchell, 1997). More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 94 publications
(150 reference statements)
2
16
0
Order By: Relevance
“…In our study, task performance will refer to the recurring set of activities or expected behaviors of an individual that are typically described by formal job descriptions (Borman & Motowildo, 1993), whereas organizational citizenship behaviors are defined as ‘individual behaviors that are discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization’ (Organ, 1988, p.4). More precisely, because little attention has been paid to the underlying psychological mechanisms linking fit perceptions to task performance and organizational citizenship behaviors (Resick, Giberson, Dickson, Wynne, & Bajdo, 2013), an important aim of this paper is to test the mediating role of organizational identification, using the Cognitive and Affective Personality System (CAPS) Theory (Mischel & Shoda, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, task performance will refer to the recurring set of activities or expected behaviors of an individual that are typically described by formal job descriptions (Borman & Motowildo, 1993), whereas organizational citizenship behaviors are defined as ‘individual behaviors that are discretionary, not directly or explicitly recognized by the formal reward system, and that in the aggregate promotes the effective functioning of the organization’ (Organ, 1988, p.4). More precisely, because little attention has been paid to the underlying psychological mechanisms linking fit perceptions to task performance and organizational citizenship behaviors (Resick, Giberson, Dickson, Wynne, & Bajdo, 2013), an important aim of this paper is to test the mediating role of organizational identification, using the Cognitive and Affective Personality System (CAPS) Theory (Mischel & Shoda, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, CWBs are behaviours directed towards the environment and/or others to lessen this discrepancy and reduce negative feelings. In a similar vein, other scholars have suggested that P–O fit’s relationship with citizenship behaviours can be explained by cognitive–affective personality system (CAPS) theory (Resick, Giberson, Dickson, Wynne, & Bajdo, 2013). This theory suggests that individuals recognise qualities of their workplace environment that have personal relevance.…”
Section: Person–organisation Fitmentioning
confidence: 85%
“…This adds to their self-evaluations and observations about themselves, increasing their perceived fit. Resick et al. (2013) also suggest that perceived fit within one’s vocation can influence the belief that the fate of the organisation is equivalent to the fate of the individual, increasing one’s motivation to enact OCBs.…”
Section: Person–organisation Fitmentioning
confidence: 99%
See 1 more Smart Citation
“…Effectuation may help in explaining how employees could effectuate the fit and how effectuating the fit might be enabled in the organization. Resick et al (2013) view the individual fit schemas unique as they vary from person to person. When knowledge is constructed in interaction, it is important to discover what is real to the individuals because it affects their behavior (Kristof-Brown and Billsberry, 2013).…”
Section: Recent Findings In Fit Researchmentioning
confidence: 99%